Penerapan Asuhan Kebidanan Pada Anak Dengan Miliariasis Di Bpm “R” Wilayah Kerja Puskesmas Pasar Ikan Kota Bengkulu - Umami, Desi Aulia (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The World Health Organization in 2016 reports that every year there are 80% of sufferers of prickly heat (Milliariasis), of which 65% occur in infants and toddlers (Setyowati, 2019). 49.6% of Indonesia's population is at risk for prickly heat (Milliariasis). Most often occur in babies, especially in big cities that are hot and stuffy. The purpose of this study was to implement and improve the writer’s ability to handle midwifery care in 18 months old children "A" with Milliariasis by using a midwifery management approach according to Varney. This research is a case study by using descriptive method, which is a method that is carried out with the main objective of making an objective description or description of a situation and determining attention to certain objects. In the case, the subjective data obtained were that the child had been fussy for 2 days and on the back there were bubbles filled with clear liquid and the arm area looked red. All planned interventions have met the outcome criteria. In this study it can be concluded that not everything that is found in the theoretical concept is found in the case because it depends on the results of the assessment of the disease state, clinical symptoms and facilities and infrastructure in the research area at the time of the assessment. This research is able to add insight to parents who have children about the importance of prevention, treatment and proper handling of toddlers with Milliariasis.